Criminal Sanctions Against Publisher of Empty Giro in Polda Jateng Jurisdictions - Ridha Ari Setyono (Jurnal Daulat Hukum, 2018)
The research titled Criminal Sanctions Against Empty Giro Publisher in POLDA Jateng Jurisdiction. The purpose of this study: 1) To determine and analyze the implementation process of the investigation against the perpetrators of criminal sanctions Empty Giro Publisher in POLDA Jateng Jurisdiction. 2) To identify and analyze the constraints and solutions in implementation investigations against perpetrators of criminal sanctions Empty Giro Publisher in POLDA Jateng Jurisdiction. Research result : 1. Law enforcement against perpetrators of criminal acts in the form of giro checks is through the efforts of repressive. Repressive efforts are attempts made by the investigator to take action against the perpetrators of criminal acts Empty Giro in the jurisdiction of the POLDA Jateng. This is done so that the Empty Giro criminal cases can be resolved legally and thus criminal checks received appropriate punishment of what they did. 2. Factors to be obstacles in the implementation of criminal investigations Empty Giro that it is difficult unresolved criminal cases Empty Giros that internal factors and external factors: a) Internal factors include the following: 1) Personnel limited police investigator 2) Factors geographical circumstances 3) Witnesses minimum 4) lack of operational budgets investigation 5) Lack of expert investigators in handling criminal cases Empty Giros. While b) External factors, mepiputi: 1) Difficulty in finding relevant legal experts in the field of criminal fraud checks. 2) The level of public knowledge are limited in banking issues and agreements giro payment by check or giro. The efforts made by POLDA Jateng investigator in the criminal prosecution of fraud in the form of a Empty Giro and giro slip is to undertake repressive efforts. 2) The level of public knowledge are limited in banking issues and agreements giro payment by check or giro. The efforts made by POLDA Jateng investigator in the criminal prosecution of fraud in the form of a Empty Giro and giro slip is to undertake repressive efforts. 2) The level of public knowledge are limited in banking issues and agreements giro payment by check or giro. The efforts made by POLDA Jateng investigator in the criminal prosecution of fraud in the form of a Empty Giro and giro slip is to undertake repressive efforts.Keywords: Criminal Sanctions; Empty Giro Publisher; POLDA Jateng